ANALISIS KEBUTUHAN LITERASI MEMBACA SISWA DI KELAS 3 SD - Putri Anjani Oktaviadialoka; Risma Nuriyanti; Rajji Koswara Adiredja (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the reading literacy needs of third-grade elementary school students, including their reading ability levels, the difficulties they face, and the efforts needed to overcome those difficulties. This research employs a qualitative approach using a literature study method. Data were collected from various sources such as books, scientific journals, and relevant research articles, and were analyzed using content analysis techniques. The results indicate that third-grade students are in the transitional stage from early reading to reading comprehension. However, several difficulties are still found, including lack of reading fluency, limited vocabulary, and low comprehension skills. These difficulties are influenced by internal factors such as low reading interest, as well as external factors such as limited variation in teaching methods and lack of supportive literacy environments.Efforts to overcome these difficulties include implementing interactive teaching methods, utilizing engaging learning media, providing continuous reading practice, and creating a conducive literacy environment. In addition, teachers need to provide special guidance for students who experience reading difficulties. Therefore, analyzing reading literacy needs is essential as a foundation for designing effective learning strategies. This study is expected to contribute to improving students’ reading literacy skills at the elementary school level.